THE HISTORY AND POTENTIAL OF ART THERAPY IN THE PREVENTION OF SOCIAL PHOBIAS OF STUDENTS (Journal of Educational Sciences, 2020)
In the article, particularities of the preventive work of social phobias of youth are considered. According to WHO, the number of children and youth with such a diagnosis has now increased. This is an important argument in favor of the need for early detection and prevention of social phobias in order to prevent severe maladaptation, the development of persistent inadequate defense mechanisms, the occurrence of concomitant diseases such as severe depression and alcoholism. Also, the characteristic indications for prevention is the inability, due to fears, to continue to study, work, form stable social ties, etc. The article suggests the periodization of the development of research on the prevention of social phobias. 3 stages are distinguished: Pre-Developmental Period, Initial Developmental Period, Recent Developments. It considers factors affecting the development of social phobias of youth. A prevention program of students’ social phobias was developed, as part of the research. 60 students of Al-Farabi Kazakh National University attended in the experiment. Diagnostics is made by LSAS method. The correction program included art-therapeutical methods, classes were conducted according to a program designed for 30 hours. The stabilization dynamics is shown after experimental and pedagogical work on the prevention of social phobias through art therapy methods. Key words: social phobia, prevention, phobia, program, preventive work, art therapy, fears, social and educational methods.